PERAN JAPAN INTERNATIONAL COOPERATION AGENCY (JICA) PASCA BENCANA ALAM 2018 DI SULAWESI TENGAH - Sulfitri Husain (SPEKTRUM, 2022)
The locus in this study is the disaster-affected area in middle Sulawesi. Palu, Sigi, and Donggala were some of the areas that were badly damaged as a result of the earthquake, tsunami and liquefaction that occurred in September 2018. In addition to the loss of life, the disaster caused several public facilities to be seriously damaged (broken electricity and telecommunications networks). School buildings, hotels, hospitals, offices, malls and several roads were badly damaged. Various national and international aids, both government and non-government, have contributed. The Japan International Cooperation Agency (JICA) is one of the international agencies involved from emergency response to recovery with a build back better concept in the Palu, Sigi, and Donggala (PASIGALA) areas. This study uses a descriptive qualitative method which will analyze the extent to which JICA's role as one of Japan's International Cooperation agencies is involved in providing post-disaster assistance. The Japan International Cooperation Agency (JICA) is one of the international agencies involved from emergency response to recovery with a build back better concept in the Palu, Sigi, and Donggala (PASIGALA) areas. In this study, in addition to primary data, secondary data in the form of books, documents, news, and journals are also complementary to the analysis. Descriptive qualitative method is used in analyzing the extent to which JICA's role as one of Japan's International Cooperation agencies is involved in providing post-disaster assistance. The results of this study explain that JICA is one of the donor agencies that has a role and several programs in reorganizing middle Sulawesi after the disaster.Keywords: Disaster Relief, International Agenc, JICA Abstrak.Lokus dalam penelitian ini adalah wilayah yang terdampak bencana di Sulawesi Tengah. Palu, Sigi, dan Donggala merupakan beberapa daerah  yang rusak parah akibat dari gempa, tsunami, dan likuifaksi yang terjadi pada September 2018 lalu. Selain korban jiwa, bencana tersebut menyebabkan beberapa fasilitas umum rusak parah (putusnya jaringan listrik dan telekomunikasi). Gedung sekolah, perhotelan, rumah sakit, perkantoran, mall dan beberapa jalan mengalami rusak parah. Berbagai bantuan nasional, internasional baik yang pemerintah dan non pemerintah berpartisipasi memberikan sumbangsihnya. Japan International Cooperation Agency (JICA) merupakan salah satu dari lembaga internasional yang terlibat mulai tanggap darurat hingga recovery dengan konsep build back better di wilayah Palu, Sigi, dan Donggala (PASIGALA). Dalam penelitian ini, selain data primer, data sekunder berupa buku, dokumen, berita, dan jurnal juga sebagai pelengkap analisis.  Metode kualitatif deskriptif yang digunakan dalam menganalisis sejauh mana peran JICA sebagai salah satu badan Kerja Sama Internasional Jepang  untuk terlibat dalam pemberian bantuan  pasca bencana. Hasil penelitian ini menjelaskan JICA merupakan sebagai salah satu lembaga pendonor yang memiliki peran dan beberapa program dalam menata kembali Sulawesi Tengah pasca bencana. Kata kunci: Bantuan Kebencanaan, Lembaga Internasional, JICA